A Reexamination of Renewable Electricity Policy in Sweden - Sven-Olof Fridolfsson; Thomas Tangerås (Research Institute of Industrial Economics (IFN), 2012)
Green certificates are the main instrument for promoting renewable electricity (RES-E) in Sweden. But certificates cover only a limited share of total RES-E production. Under partial coverage, crowding out may arise whereby costly new RES-E replaces inexpensive old RES-E. Granting certificates to all of RES-E production improves efficiency, but leaves windfall rent to otherwise profitable facilities. We also analyze transaction costs in the permit process for new RES-E in Sweden. Municipalities veto socially desirable projects because of asymmetrically distributed investment costs and benefits. We propose market-based permit fees rather than limited veto rights as a solution to this NIMBY problem.
Keywords: D23; Q48; Q52; Q54; 330; Crowding out; Green certificates; NIMBY; Transaction costs; Windfall rent; Erneuerbare Energie; Förderung erneuerbarer Energien; Verdrängungseffekt; Betrieblicher Standort; Transaktionskosten; Schweden